PERCEPTION OF MOTOR VEHICLE TAXPAYERS (PKB) IN PAYING TAXES IS SEEN FROM THE POINT OF VIEW OF SKEPTICISM - Wahyuni, Amalia (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Skepticism in paying taxes is a view for taxpayers in atendency to a dubious attitude in making tax payments. The purpose of this study is to determine the perception of motor vehicle taxpayers (PKB) in paying taxes and the emergence of skepticism in paying taxes. The theory of planned behavior (SDGs) was used in this study. The type of research data used is qualitative data. The data obtained is in the form of information obtained through interviewsand research informants. Data primary and secondary data are the data sources used. The results of the study according to taxpayers that they consider that the obligation to pay taxes is a contribution to the government whose benefits cannot be felt directly or quickly. Based on the theoretical aspect of planned behavior, in the variable attitude towards taxpayer behavior there isa tendency to be unhappy or negative, this results in a greater emergence of skepticism in taxpayers. There is a taxpayer’s belief that the difficulty if not paying taxes is a form of behavioral control because to control the behavior of the taxpayer requires examination and supervision. Basically, the actual condition of the occurrence of doubts about paying taxes is not supported by subjective norms, this raises doubts about paying taxes not solelydue to social pressures, especially the Covid 19 virus that has hit our homeland. The existence of beliefs from within the individual causes a tendency to appear skepticism in the behavior of paying taxes formed by attitudes towards the behavior and control of the perceived behavior.